Identification of important factors for office space decision by tenants in Kuala Lumpur city centre, Malaysia - experts' view - Mohd Adnan, Y.; Daud, M.N. (2010)
While the central business district (CBD) in most cities is referred to as the heart of the city, the development strategy within the Kuala Lumpur city centre area is to have a moderate commercial growth. This is to curb the oversupply of commercial space and attracting quality development with the aim of enhancing Kuala Lumpur's role as an international and financial centre. As the Kuala Lumpur city centre has the most concentration of office space in Malaysia, it would be useful to identify the factors which would attract and retain tenants for the existing office buildings in the area. It has been noted from various studies on office occupation in the central business district (CBD), different factors influence the decision. In the preliminary part of a study to identify the factors influencing tenants' decision in office occupation, the view of experts' were sought. This paper highlights the findings of a survey among property consultants/agents and property/leasing managers in which the main important factors are identified. This result will then be used into the study for the determination of the relative importance of the factors and sub-factors across the different categories of office buildings' tenants in Kuala Lumpur city centre.